Efeitos do ensino de relações entre fonemas, grafemas e imagens e do treino de junção de fonemas no desempenho em leitura recombinativa em uma instrução em grupo - Guimarães, Luisa Schivek (2019)
This research aimed to investigate the effect of teaching relationships between phonemes, graphemes and images of subjects/objects which utter phonemes, along with the training of phonemes junction, in the development of reading comprehension, receptive reading and textual behavior of words recombination in children whom have not yet been literate and in a context of collective instruction. Study 1 was conducted with four children whom attended the first year of an elementary municipal school in São Paulo and whom presented difficulties in literacy, one of them was a participant-control in a multiple baseline delineation. The teaching stages were: 1. presentation of the grapheme with the corresponding phoneme and figure, followed by the children's echoic response; 2. matching to sample of the phoneme with the corresponding figure and the figure with the corresponding grapheme; 3. arbitrary constructed response matching to sample of syllables (dictation with help of the figures); 4. textual behavior of syllables with fading out of auxiliary stimuli; 5. individual textual behavior of syllables; 6. matching to sample of the spoken syllable with the written syllable; 6. individual mixed block of textual behavior of syllables; 7. arbitrary constructed response matching to sample of words (dictation with help of the figures); 8. textual behavior of words with fading out of auxiliary stimuli; 9. textual behavior of words performed individually and 10. matching to sample of the spoken word with the written word. All participants presented emergency of textual behavior and receptive reading in front of recombination words, and only one did not present emergency of reading with comprehension. In some situations, textual responses were given to stimuli that contained minimal units uninstructed. A second study was conducted with the aim of producing greater control of variables. Five children whom attended the last year of Early Childhood Education (and whom were not systematically submitted to literacy procedures) participated in Study 2, one of whom was not exposed to teaching and one was a participant-control in a design of multiple baseline. During teaching, the participants uttered the phonemes with pauses between them. Echoic models were provided and children were required to utter phonemes at the exact moment of the indication of the corresponding graphemes. Among the four participants exposed to teaching, it was observed the emergence of textual responses to recombination words for three (only one, whom did not complete the study, did not present them); receptive reading words of recombination for all participants, and reading comprehension for two of them. The results from the control participants suggested that these changes in performance were produced by the adopted procedures. Comparison with the results of previous studies using phonic instruction indicated that the use of images representing subjects / objects that utter phonemes and phoneme junction training may be effective strategies to decrease the variability of results among participants and increase recombinative reading rates